1997
DOI: 10.1097/00006123-199706000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic Sarcoma of the Spine in Nonleukemic Patients: Report of Three Cases

Abstract: Granulocytic sarcomas in nonleukemic patients are rare, and when they affect the spine they are frequently misdiagnosed. Appropriate therapy for these tumors requires early identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
1
23
0
6
Order By: Relevance
“…Five patients finally diagnosed as AML, and 4 of these 5 patients died within a relatively short time (mean 11 months). 8,13,24,25) On the other hand, among the 5 patients who did not develop AML, only one patient died. 23) Retrospectively, our patient showed the typical manifestation of pediatric spinal epidural granulocytic sarcoma preceding clinical manifestation of leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five patients finally diagnosed as AML, and 4 of these 5 patients died within a relatively short time (mean 11 months). 8,13,24,25) On the other hand, among the 5 patients who did not develop AML, only one patient died. 23) Retrospectively, our patient showed the typical manifestation of pediatric spinal epidural granulocytic sarcoma preceding clinical manifestation of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,12,13,16,21,[23][24][25] Nine of the 10 patients were males, and the mean age was 11 years. The male predominance might be associated with the higher incidence of AML in males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore we have demonstrated that on transplantation to syngeneic mice, the cell line will only form lethal sarcomas in vivo, with nearly undetectable numbers of circulating leukemic cells evident. In humans, myeloid sarcomas, also called chloromas, are a very rare presentation in leukemic malignancies or pre-leukemic states, and are most commonly associated with myeloproliferative or myelodysplastic syndromes in progression to genuine leukemia (Deme et al, 1997). Since our model exclusively forms myeloid sarcomas, it is likely to prove useful in studying molecular processes of transformation leading to myeloid sarcoma development.…”
Section: Discussionmentioning
confidence: 99%